2019
DOI: 10.1590/2177-6709.24.4.33.e1-8.onl
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of shear bond strength of orthodontic brackets bonded with a universal adhesive using different etching methods

Abstract: Objective: The aim of this study was to compare the effects of three enamel etching modes - laser-etch, self-etch and acid-etch (5, 10 and 15 s) - on bracket bonding, using a universal adhesive. Methods: Eighty-four maxillary premolars were randomly divided into seven groups (n=12) based on the etching method and the adhesive used for bracket bonding. After water storage and thermocycling, shear bond strength was measured, and adhesive remnant index scores on debonded enamel were determined. Results: There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 33 publications
1
24
7
Order By: Relevance
“…27 In agreement with this study, it has been concluded that Scotchbond Universal showed higher bond strength than Transbond XT, and this resulted from the 10-MDP monomer. 6 The main functional monomer of Prime&Bond Universal is PENTA. In a previous study, Prime&Bond Universal presented similar bond strengths when compared with Scotchbond Universal.…”
Section: Discussionmentioning
confidence: 99%
“…27 In agreement with this study, it has been concluded that Scotchbond Universal showed higher bond strength than Transbond XT, and this resulted from the 10-MDP monomer. 6 The main functional monomer of Prime&Bond Universal is PENTA. In a previous study, Prime&Bond Universal presented similar bond strengths when compared with Scotchbond Universal.…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting study by Shafiei et al (21) , concluded that the usage of universal adhesives was the tipping point in enhancing the shear bond strength of orthodontic adhesive systems to permanent enamel, whether used with acid etching or laser etching without any significant difference between the two methodologies. The authors explained that the presence of 10-MDP copolymer in universal adhesives has been documented to be capable of bonding to enamel and dentin effectively, forming a nano-layer at the adhesive interface.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Bahrololoomi et al (21) , stated that if laser is to be used for tooth preparation, it must be necessarily accompanied by acid etching. And that the maximum bond strength values relative to their study groups belonged to bur and acid-etching preparation in dentin and enamel followed by laser preparation and etching; and laser preparation followed by resin bonding without etching resulted in the lowest bond strength.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations